Filosofía africana de la educación: por una cartografía de la encrucijada (2022)
The article presents an African philosophy of education from the cartography of the crossroad of African philosophies. The timid dialogue of the philosophies from the African experiences in the Brazilian philosophy of education is observed in the fight to the black African in the political project of Brazil. Therefore, it problematizes the epistemological cloistering from the cartography of the crossroad in the critique and the overcoming of cultural semiocide and epistemicide, which points to a decolonization in the sense of educating.